Anglicans, Dissenters and Radical Change in Early New England, 1686–1786 - Bell, James B. author. aut Link
XXV, 280 p. 39 illus.
Keywords: This book considers three defining movements driven from London and within the region that describe the experience of the Church of England in New England between 1686 and 1786. It explores the radical imperial political and religious change that occurred in Puritan New England following the late seventeenth-century introduction of a new charter for the Massachusetts Bay Colony, the Anglican Church in Boston and the public declaration of several Yale ‘apostates’ at the 1722 college commencement exercises. These events transformed the religious circumstances of New England and fuelled new attention and interest in London for the national church in early America. The political leadership, controversial ideas and forces in London and Boston during the run-up to and in the course of the War for Independence, was witnessed by and affected the Church of England in New England. The book appeals to students and researchers of English History, British Imperial History, Early American Historyand Religious History.